Economics of Cancer Medicines: For Whose Benefit?. Issue 1 (2nd January 2017) - Gyawali, Bishal; Sullivan, Richard
Abstract : Although new cancer drugs are continually getting approved and used, the value that these drugs add is very debatable. Because of the skyrocketing cost of the new drugs, each new approval represents a multibillion market. However, unlike other branches of economics, cancer drugs are intricately associated with socio-political issues, emotional overlay, public pressure, industry manipulation and propaganda. In this article, we review the value added by new cancer drugs and examine the socio-political agenda around them with highlights on the increasing gulf between high-income and low-middle income countries regarding the affordability to these drugs. Finally, we also suggest a way forward to address this highly complex issue.